How terrorist groups end : lessons for countering Al Qa'ida - Jones, Seth G., 1972- (Rand, 2008)
All terrorist groups eventually end. But how? Most modern groups have ended because they joined the political process or local police and intelligence agencies arrested or killed key members. This has significant implications for dealing with al Qa'ida and suggests fundamentally rethinking post-9/11 U.S. counterterrorism strategy: Policing and intelligence, not military force, should form the backbone of U.S. efforts against al Qa'ida.